PENGARUH FAKTOR WORKING CAPITAL TERHADAP FIRM PERFORMANCE DIMODERASI OLEH NET LIQUID BALANCE - Wijaya, Agustina; Imelda, Elsa (Jurnal Paradigma Akuntansi, 2024)
The research was conducted with the aim to find the effect of firm age, cash flow, firm size, leverage, and sales growth on firm performance with net liquid balance as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The sample in this study was 252 companies data obtained through purposive sampling method. The data processing process used the EViews 12 application and Microsoft Excel 2019. This research obtained the results that firm age, cash flow, salse growth and leverage significantly affect firm performance. Meanwhile, firm size has no effect on firm performance. The study also shows that the net liquid balance is only able to moderate the effect of cash flow, leverage, and sales growth on firm performance. The implication of this research is that management must manage and use the company's resources to the maximum and maintain the company's NLB level to create maximum company performance.